Cancer screening in France: third edition of the EDIFICE survey. (June 2015) - Viguier, Jérôme; Morère, Jean-François; Touboul, Chantal; Coscas, Yvan; Blay, Jean-Yves; Lhomel, Christine; Pivot, Xavier; Eisinger, François
Abstract : The EDIFICE programme began in 2005 and set out to provide a clearer insight over time into the participation of the French population in cancer screening. EDIFICE 3 was conducted in 2011 by phone interviews among a representative sample of 1603 individuals aged between 40 and 75 years using the quota method. The analysis focused on the target populations (50–74 years) of the national screening programmes for breast and colorectal cancer. The same populations were also assessed with respect to prostate cancer screening. In 2005, 93% of the sample population had undergone at least one mammogram in their lifetime; this figure reached 94% in 2008 and 95% in 2011. Compliance with recommended intervals improved between 2005 and 2011, and significantly so for women aged 65–74 years. In 2005, 25% of respondents reported having undergone at least one colorectal cancer screening test; this figure reached 38% in 2008 and 59% in 2011. Recommended intervals were respected by 30 and 51% in 2008 and 2011, respectively. In 2005, 2008 and 2011, a total of 36, 49 and 50% of men reported having undergone at least one prostate cancer screening test. This rate decreased significantly in men aged 50–59 years between 2008 and 2011 (44 vs. 37%, P ⩽0.05). Attendance rates in national screening programmes are high and stable for breast cancer, and although currently improving for colorectal cancer, the European guideline target has not yet been reached. Despite the absence of recommendations for prostate cancer screening, participation remains constant.